Optimization of Quercetin‐Assisted Silver Nanoparticles Synthesis and Evaluation of Their Hemocompatibility, Antioxidant, Anti‐Inflammatory, and Antibacterial effects. Issue 12 (20th October 2021) - Chahardoli, Azam; Hajmomeni, Pouria; Ghowsi, Mahnaz; Qalekhani, Farshad; Shokoohinia, Yalda; Fattahi, Ali
Abstract: In the present study, different effective parameters (temperature, reaction time, and pH) on the synthesis of quercetin‐assisted silver nanoparticles (QE‐AgNPs) are optimized. These biogenic NPs are characterized by different physico‐chemical analyses, including transmission electron microscopy, X‐ray diffraction, Fourier transform infrared (FTIR) spectroscopy, and UV‐visible spectroscopy. In addition, the biological properties of QE‐AgNPs are evaluated through antioxidant, antimicrobial, anti‐inflammatory, hemolysis, and coagulation time assays. The formation of QE‐AgNPs is affected by different parameters. The optimum condition for the synthesis of QE‐AgNPs is attained at 70 °C and pH 7. Prepared QE‐AgNPs show a spherical shape with a crystalline nature and an average particle size of 20 ± 3.6 nm. The role of QE as a reducing and capping agent in the preparation process of QE‐AgNPs is demonstrated using FTIR analysis. These NPs with excellent antioxidant activity (82.3% at a concentration of 400 µg mL −1 ) and anti‐inflammatory properties (82.5% and 100% at concentrations of 37.25 and 500 µg mL −1, respectively), show good antimicrobial effects, particularly against Staphylococcus aureus . Furthermore, the results of the hemolytic and coagulation assay of QE‐AgNPs indicate their hemo‐compatibility. Therefore, hemo/bio‐compatible QE‐AgNPs with excellent and unique properties can be employed in different medicinal and pharmacological applications. Abstract : In the current study, the optimal conditions for the synthesis of quercetin‐assisted silver nanoparticles (QE‐AgNPs) and their biological properties are investigated. Spherical QE‐AgNPs (20 ± 3.6 nm) with excellent anti‐inflammatory properties, blood compatibility, and antioxidant activity are effective against bacterial strains, particularly Staphylococcus aureus . Therefore, these NPs with unique properties can be a suitable option for various medicinal applications.